PREVALENSI HBsAg POSITIF PADA PENDONOR DARAH DI UNIT DAERAH PALANG MERAH INDONESIA LOMBOK BARAT - Kisniarti, Linda; Sukmana, Dhika Juliana; Aini, Aini; Alfisahrin, Alfisahrin; Halid, Idham (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
Hepatitis B virus infection is the main cause of acute and chronic hepatitis, cirrhosis and liver cancer, 25% of whom experience jaundice. Blood transfusion is one of the most common routes of HBV transmission. The purpose of this study was to determine the prevalence of reactive and non-reactive HBsAg in the West Lombok Indonesian Red Cross unit. This type of research is descriptive, carried out in June 2022 at the West Lombok Indonesian Red Cross Unit. The results showed that the largest number of donors were men (12,201 people) and the age group of 25-44 years (4,342 people). Based on the results of the HBsAg examination, the prevalence of positive HBsAg in men was 76% and 24% in women.